Muhammad Usman

235 Reputation

5 Badges

11 years, 201 days
Beijing, China

MaplePrimes Activity


These are replies submitted by Muhammad Usman

@Carl Love 

Dear Sir I want to plot the above graph from -1..1 where the change will happen? I am waiting your positive response. 

@John Fredsted I required a sepcial lower triangular matrix as shown in attached fine. I know the built-in command which you sent me. If you fix my problem, i will be grateful to you. Thanks

@AmusingYeti 

First I am very thankful to you about your valuable comments. Now I am facing another problem in integration please see the attachment and fixed it as soon as possible. I am waiting your kind comments. Take crae.

Integration.mw

@tomleslie 

Dear how you get this solution, which command you used? Please correct the attached file and send me back. I am waiting your kind response.

@Markiyan Hirnyk 

I do not understand your question what you want to say.

@tomleslie 

eta=1

@Carl Love 

Sorry! I was busy last three days, didnt check your mail, first I will checked then let you know. Thanks

@vv 

Dear Sir please help me to complete this program of square free factrization whose explanation below

Let

 f = x^{11} + 2 x^9 + 2x^8 + x^6 + x^5 + 2x^3 + 2x^2 +1 \in \mathbf{F}_3[x],

to be factored over the field with three elements.

The algorithm computes first

 c = \gcd(f, f') = x^9 + 2x^6 + x^3 + 2.

Since the derivative is non-zero we have w = f/c = x2 + 2 and we enter the while loop. After one loop we have y = x + 2, z = x + 1 and R = x + 1 with updates i = 2, w = x + 2 andc = x8 + x7 + x6 + x2+x+1. The second time through the loop gives y = x + 2, z = 1, R = x + 1, with updates i = 3, w = x + 2 and c = x7 + 2x6 + x + 2. The third time through the loop also does not change R. For the fourth time through the loop we get y = 1, z = x + 2, R = (x + 1)(x + 2)4, with updates i = 5, w = 1 and c = x6 + 1. Since w = 1, we exit the while loop. Since c ≠ 1, it must be a perfect cube. The cube root of c, obtained by replacing x3 by x is x2 + 1, and calling the square-free procedure recursively determines that it is square-free. Therefore, cubing it and combining it with the value of R to that point gives the square-free decomposition

 f= (x+1)(x^2+1)^3(x+2)^4.
New.mw

@Carl Love 

Dear Sir! I am waiting your kind response

@Carl Love 

Dear sir first of all very thansful for your nice cooperation. The above program give roungh result like

Let

 f = x^{11} + 2 x^9 + 2x^8 + x^6 + x^5 + 2x^3 + 2x^2 +1 \in \mathbf{F}_3[x],

to be factored over the field with three elements.

The algorithm computes first

 c = \gcd(f, f') = x^9 + 2x^6 + x^3 + 2.

Since the derivative is non-zero we have w = f/c = x2 + 2 and we enter the while loop. After one loop we have y = x + 2z = x + 1 and R = x + 1 with updates i = 2w = x + 2 andc = x8 + x7 + x6 + x2+x+1. The second time through the loop gives y = x + 2z = 1R = x + 1, with updates i = 3w = x + 2 and c = x7 + 2x6 + x + 2. The third time through the loop also does not change R. For the fourth time through the loop we get y = 1z = x + 2R = (x + 1)(x + 2)4, with updates i = 5w = 1 and c = x6 + 1. Since w = 1, we exit the while loop. Since c ≠ 1, it must be a perfect cube. The cube root of c, obtained by replacing x3 by x is x2 + 1, and calling the square-free procedure recursively determines that it is square-free. Therefore, cubing it and combining it with the value of R to that point gives the square-free decomposition

 f= (x+1)(x^2+1)^3(x+2)^4.
but the program given
(x+1)*(x+2)^4*(x^6+1)
Recheck.mw

@Carl Love 

Dear sir please try by taking p = 3. I am waiting your response as I need urgent.

@Carl Love 

p=3

@ThU 

Dear, I already doing same procdure but this particular solution is rongh, the correct one has attached

@Carl Love 

This algorithm is not run. Please send its maple file

First 8 9 10 11 Page 10 of 11